Effects of BCAA supplementation on plasma and mare's milk amino acid contents in Yili mares and growth performance of suckling foals - Ren, Xiang; Xue, Yuheng; Shen, Zhehong; Liu, Xiaotian; Chang, Xiaokang; Meng, Jun; Ren, Wanlu; Wang, Jianwen; Yao, Xinkui; Zeng, Yaqi (Frontiers in Veterinary Science, 2025)
Branched-chain amino acids (BCAAs) play a crucial role in regulating nutritional metabolism in lactating animals. However, limited research has been conducted on BCAAs in equines. This study aimed to investigate the effects of different doses of BCAA supplementation on plasma and milk amino acid profiles in Yili mares, as well as the growth performance of their suckling foals, thereby providing a scientific basis for optimizing feeding management practices. Eighteen pairs of Yili mares and their sucklings were randomly assigned to four groups: a control group (Group D, no BCAA supplementation) and three experimental groups (S1, S2, and S3, receiving 38 g/day, 76 g/day, and 114 g/day of BCAA supplementation, respectively). The trial lasted for 67 days. The concentrations of 22 amino acids in plasma and milk were quantified using liquid chromatography-mass spectrometry (LC-MS), and their correlations with the body height, length, and weight of the foals were analyzed using SPSS software (one-way analysis of variance and Pearson correlation test). In mare plasma amino acids, the serine (Ser) content in group S1 was significantly higher than that in group D (p < 0.05). Additionally, in group S3, tryptophan (Trp), histidine (His), and aspartic acid (Asp) contents were markedly elevated. For mare milk amino acids, Ser content in group S1 was extremely significantly higher than in group D (p < 0.01), while aspartic acid (Asp) and alanine (Ala) contents were significantly increased in group S3. Regarding foal growth performance, body weight in group S3 was significantly greater than in group D. Moreover, group S2 exhibited superior trends in body height and length growth. Correlation analysis demonstrated that plasma Ser and creatine (Cr) were positively correlated with mare milk Ser and Cr. Mare milk threonine (Thr) showed a positive correlation with foal body height and length. Studies indicate that branched-chain amino acids (BCAA) regulate protein synthesis and amino acid metabolism via the mTOR pathway. In this experiment, 38 g/d BCAA enhanced mammary gland Ser transport, thereby increasing its content. Furthermore, 114 g/d BCAA promoted Asp and Ala accumulation, likely due to enhanced catabolic activity. The positive correlation between mare milk Thr, His, and skeletal development suggests that BCAA indirectly promotes growth through milk composition regulation. However, given the small sample size of this study, long-term validation is necessary.